Characteristic of graphene-based thick film gas sensor for ethanol and acetone vapor detection at room temperature - Mohd Chachuli, Siti Amaniah; Noor, Muhammad Luqman Hakkim; Coban, Omer; Shamsudin, Nur Hazahsha; Idris, Muhammad Idzdihar (Institute Of Advanced Engineering And Science (IAES), 2023)
Ethanol and acetone are volatile organic compound gases widely used in food processing. Health problems such as irritation of the eyes, nose, and throat can affect human health if exposed to these gases. Two graphene gas sensors were fabricated using a screen-printing technique onto a glass substrate to compare their performance to the acetone and ethanol vapors at room temperature. The graphene paste was prepared by mixing 95 wt.% of the binder with 5 wt.% of graphene nanoflakes. A silver paste was used as the interdigitated electrode of the gas sensor and became the first layer of the gas sensor. The silver paste was deposited on the glass substrate using a screen-printing technique and fired at 150 °C for 15 minutes. Next, the graphene paste was deposited onto the interdigitated electrode using a screen-printing technique and became the second layer of the gas sensor. The graphene was annealed at 200 °C for 30 minutes. Both graphene gas sensors responded well to ethanol and acetone vapor with an n-typed gas sensor at room temperature. As a comparison, the graphene gas sensor showed better characteristics in terms of response and recovery characteristics to ethanol vapor than acetone vapor at room temperature. The response and response time of the graphene-based thick film gas sensor to ethanol were approximately 21.89 and 24.08, respectively.